(3ELGRg dGHi WGgQ GdSdaj GdGScfOQis - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3Ef QCi GdTjN GdGLd GdYGde GdYdGeI GOGe Gddg Jhajbg Gf fNHQ LejY SeGYGJg hGLGRGJg hQhGjGJg heG Gda ai afhf GdYde hGfTCg ef GdebGeGJ hGdQSGFd hGdTYQ s
(3BNQgG (B:s
(3ce NdUJ GdML GdHMQ GdQLGd heG Gbd ef NdUJg gPg GddLL ChKb ef cfGfJi hGdMeO ddg GhdkG hBNQkG hGdUdGI Ydi fHjg eMeO hBdg GLeYjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQdi (B(1210 / 5) s
Keywords: (3GdMOjK h GdeUWdMs